2020
DOI: 10.1101/2020.06.19.161067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study in European patients with congenital heart disease identifies risk loci for transposition of the great arteries and anomalies of the thoracic arteries and veins and expression of discovered candidate genes in the developing heart

Abstract: Rationale: Genetic factors undoubtedly contribute to the development of congenital heart disease (CHD), but still remain mostly ill-defined.Objective: Identification of genetic risk factors associated with CHD and functional analysis of SNPcarrying genes. , 2,594 patients of previous studies provided by the Newcastle University and 8,486 controls underwent meta-analysis to detect single nucleotide polymorphisms (SNPs) associated with CHD.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Previously identified in GWAS of blood pressure(37, 38) and aortic root diameter(38), the two variants in GOSR2 identified in systole (rs6504673) and diastole (rs533030436) display essentially no linkage in European populations (R2 0.02) and arise from different haplotypes [Figure S9]. The variant rs533030436 identified in diastolic measures is in strong linkage with rs11874 (R 2 0.84) recently identified in congenital cardiovascular malformations(39) as well as rs17608766 (R 2 0.76) identified in Aortic valve stenosis(27) in the same UK Biobank MRI dataset. The cusps and annulus of the mitral valve are composed primarily of endothelial cells and valvular interstitial cells which may differentiate to myofibroblasts in disease states(40).…”
Section: Discussionmentioning
confidence: 87%
“…Previously identified in GWAS of blood pressure(37, 38) and aortic root diameter(38), the two variants in GOSR2 identified in systole (rs6504673) and diastole (rs533030436) display essentially no linkage in European populations (R2 0.02) and arise from different haplotypes [Figure S9]. The variant rs533030436 identified in diastolic measures is in strong linkage with rs11874 (R 2 0.84) recently identified in congenital cardiovascular malformations(39) as well as rs17608766 (R 2 0.76) identified in Aortic valve stenosis(27) in the same UK Biobank MRI dataset. The cusps and annulus of the mitral valve are composed primarily of endothelial cells and valvular interstitial cells which may differentiate to myofibroblasts in disease states(40).…”
Section: Discussionmentioning
confidence: 87%
“…ZBTB10 encodes a telomere-associated protein [23]. Lately, a GWAS involving 4,000 unrelated Caucasian patients diagnosed with CHD indicated that ZBTB10 was associated with TGA, since two highly signi cant SNPs (rs148563140 and rs143638934) closely located to this gene [24]. Furthermore, they suggested strong cell-type speci city in murine cardiac development for Zbtb10.…”
Section: Discussionmentioning
confidence: 99%
“…ZBTB10 encodes a telomere-associated protein [41]. Lately, a GWAS involving 4,000 unrelated Caucasian patients diagnosed with CHD indicated that ZBTB10 was associated with TGA, since two highly significant SNPs (rs148563140 and rs143638934) closely located to this gene [42]. Furthermore, they suggested strong cell-type specificity in murine cardiac development for Zbtb10.…”
Section: Discussionmentioning
confidence: 99%